2018
DOI: 10.1590/2175-623676887
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Students’ Mathematical Argumentation in a Primary Classroom

Abstract: -The Development of Students' Mathematical Argumentation in a Primary Classroom 1 . The use of valid argument does not come naturally. It is acquired only through practice. This study was accomplished to provide students intended opportunities of engaging activities for launching argumentation in primary classrooms. The focus of the paper is how argumentation was evolved when students engaged in the conjecturing incorporated into regular mathematics instruction over two consecutive years. Working with a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
9
0
11
Order By: Relevance
“…"In an expected classroom where the young students develop skills of persuasive arguments, instead of being an audience for the teachers' reasoning, but needs to provide students the opportunities to learn such argumentation." (Lin, 2018(Lin, , p. 1174.…”
Section: Discussionmentioning
confidence: 99%
“…"In an expected classroom where the young students develop skills of persuasive arguments, instead of being an audience for the teachers' reasoning, but needs to provide students the opportunities to learn such argumentation." (Lin, 2018(Lin, , p. 1174.…”
Section: Discussionmentioning
confidence: 99%
“…One of his principal findings is that argumentation at the primary school level has a basic structure (the core of argumentation) formed by three elements from Toulmin's model (Toulmin, ): data, conclusion, and warrant. In contrast to Krummheuer's findings, other researchers have found that students in elementary school are able to construct mathematical arguments using all the elements of Toulmin's model (Cervantes‐Barraza & Cabañas‐Sánchez, ; Cervantes‐Barraza, Cabañas‐Sánchez, & Reid, ; Knipping & Reid, ; Lin, ).…”
Section: Literature Reviewmentioning
confidence: 56%
“…Argumentation as a kind of classroom discourse is useful for developing mathematical knowledge that takes place in classroom conversations and can facilitate the development of learners' knowledge of subject matter (Uygun & Akyuz, 2019). Knowledge in argumentation is also important for logical comprehension and effective communication (Lin, 2018). Moreover, argumentation in mathematics is an essential part of the mathematics discipline and a key indicator of mathematical competence (Graham & Lesseig, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to research in international perspective, in the field of science education, numerous research studies focused on the description of argumentation and the empirical investigation of the argumentation structure or the advancement of argumentative skills in science lessons in schools (Heitmann et al, 2014), whereas the reforms of the curriculum in mathematics education have given rise to an emerging research program on teaching and learning argumentation at various grade levels (Lin, 2018). Particularly, Argumentation at primary and secondary schools has been extensively discussed as a significant way to facilitate learning through the development of social and cognitive processes (Dovigo, 2016).…”
Section: Introductionmentioning
confidence: 99%